Tingkat Pengetahuan dan Produk Halal dalam Keputusan Pembelian Makanan Halal - Tri Nur Fadilah; Purwanto; Achmad Nur Alfianto (Jurnal Bisnis dan Kewirausahaan, 2022)
This study aims to identify the effect of the level of knowledge and halal products in purchasing decisions in the Windusari District. This study collects data through an online survey by distributing questionnaires from google form. Samples were taken as many as 150 people in the Windusari sub-district, aged from 17 - > 40 years, had been selected based on purposive sampling. Data analysis using SPSS. The results of this study prove that the level of knowledge has a positive and significant effect on purchasing decisions for halal food. Meanwhile, halal products have a positive and significant effect on purchasing decisions for halal food.